KEPRIBADIAN TOKOH UTAMA FILM CRYPTO BOY (2023) KARYA SHADY EL-HAMUS: KAJIAN PSIKOLOGI SASTRA - Cahyani, Ludfi Dwi, -; Pesulima, Barbara Elisabeth Lucia (Multikultura, 2026)
The film Crypto Boy (2023), directed by Shady El-Hamus has received many interesting reviews from film critics. This film raises issues about crypto investment, which is currently popular among modern society. Cryptocurrency is digital money used for online payments, and crypto transactions are always conducted through a system called “blockchain”. Blockchain is a secure and organized pathway that ensures every crypto transaction is properly recorded and protected. This film tells the story of Amir’s life as a courier who dreams of success through the world of cryptocurrency. In his journey to explore the world of crypto, Amir eventually fell victim to a crypto investment scam. The various challenges that arose from this situation contributed to the changes in Amir’s personality. The research question is: How are the personality dynamics of the main character in the film Crypto Boy (2023) by Shady El-Hamus? The purpose of this research is to describe the personality dynamics of the main character, Amir. The method used in this research is a descriptive qualitative method. The theory used is Sigmund Freud’s psychoanalytic theory of the id, ego, and superego. That psychoanalytic theory is also supported by William McDougall’s opinion, which discusses basic human instincts. The results of this research show that there are changes in Amir’s personality traits, namely from id to ego, id to ego then to superego, id to superego, and id to superego then to ego. Personality changes in the main character can make a film interesting to watch. This is because these changes can present an emotional journey, present meaningful conflicts, reflect human reality, and strengthen the film’s moral message. This research presents a deeper understanding of the personality changes of the main character in the film Crypto Boy (2023)..